Willingness for Active Case Finding of Tuberculosis among Community Pharmacists in Puducherry - Dhanajayan Govindan; Palanivel Chinnakali; Sonali Sarkar; Govindarajan Soundappan (Indian Journal of Public Health)
Background: In India, there is significant attrition in the cascade of care for tuberculosis (TB) in the public health sector. Pharmacy being the first point of contact for the majority holds considerable potential in reducing this attrition. Objectives: The objective of this study was to determine the willingness of pharmacists to screen and refer presumptive TB patients and understand challenges and enabling factors for the same. Materials and Methods: A sequential explanatory mixed-method study was conducted among pharmacies of Puducherry. Willingness to refer presumptive TB patients and collect sputum samples was summarized as proportions with 95% confidence interval. Log binomial regression was done to study the association of pharmacists’ characteristics with willingness to refer. In-depth interviews with pharmacists were transcribed; manual content analysis with hybrid coding was done. Results: Among the 202 pharmacists interviewed, 99.0% were willing to refer, 37.1% were willing to collect sputum samples, and 42.6% had ever referred a patient in the past. Patients’ lack of awareness, busy hours, and overuse of over-the-counter drugs hindered referral, while availability of quality diagnostic and treatment services, relationship with clients, and pharmacist’s knowledge facilitated referral. Conclusion: Willingness to refer patients for TB diagnosis was high among pharmacists. The national program should consider the engagement of pharmacists for improving screening and referral.